Attitudes of Physicians Towards the Care of Critically Ill Elderly Patients - a European Survey - Guidet, B (2018)
Background: Very elderly patients are one of the fastest growing population in ICUs worldwide. There are lots of controversies regarding admission, discharge of critically ill elderly patients, and also on treatment intensity during the ICU stay. As a consequence, practices vary considerably from one ICU to another. In that perspective, we collected opinions of experienced ICU physicians across Europe on statements focusing on patients older than 80. Methods: We sent an online questionnaire to the coordinator ICU physician of all participating ICUs of an recent European, observational study of Very old critically Ill Patients (VIP1 study). This questionnaire contained 12 statements about admission, triage, treatment and discharge of patients older than 80. Results: We received answers from 162 ICUs (52% of VIP1-study) spanning 20 different European countries. There were major disagreements between ICUs. Responders disagree that: there is clear evidence that ICU admission is beneficial (37%); seeking relatives' opinion is mandatory (17%); written triage guidelines must be available either at the hospital or ICU level (20%); level of care should be reduced (25%); a consultation of a geriatrician should be sought (34%) and a geriatrician should be part of the post-ICU trail (11%). The percentage of disagreement varies between statements and European regions. Conclusion: There are major differences in the attitude of European ICU physicians on the admission, triage and treatment policies of patients older than 80 emphasizing the lack of consensus and poor level of evidence for most of the statements and outlining the need for future interventional studies.